Linked open data for new library services: the example of data.bnf.fr - Romain Wenz (JLIS.it, 2013)
The Bibliothèque nationale de France (BnF) develops a new project, bringing together data from catalogues (MARC), archives (EAD) and digital resources (DC). It makes links and publishes web pages, available at http://data.bnf.fr, with already about 750.000 linked resources. All the raw data is also displayed in RDF and available with an open licence. The presentation will explain the importance of authority files and identifiers to build this kind of service, an give a first feedback on how users have been reacting to it: what kind of content is being used.